The efficacy and safety of Ginkgo biloba extract as an adjuvant in type 2 diabetes mellitus patients ineffectively managed with metformin: a double-blind, randomized, placebo-controlled trial - Aziz TA; Hussain SA; Mahwi TO; Ahmed ZA; Rahman HS; Rasedee A (Dove Medical Press, 2018)
Tavga Ahmed Aziz,1 Saad Abdulrahman Hussain,2 Taha Othman Mahwi,3 Zheen Aorahman Ahmed,1 Heshu Sulaiman Rahman,4–6 Abdullah Rasedee6 1Department of Pharmacology and Toxicology, College of Pharmacy, University of Sulaimani, Sulaimani City, 2Department of Pharmacology and Toxicology, Faculty of Pharmacy, Al-Rafidain University, Baghdad, 3Department of Medicine, College of Medicine, 4Department of Clinic and Internal Medicine, College of Veterinary Medicine, University of Sulaimani, 5Department of Medical Laboratory Sciences, College of Health Sciences, Komar University of Science and Technology, Chaq-Chaq-Qularaisi, Sulaimani City, Iraq; 6Department of Veterinary Laboratory Diagnosis, Faculty of Veterinary Medicine, Universiti Putra Malaysia, Selangor, Malaysia Background and aim: Type 2 diabetes mellitus (T2DM) is one of the major diseases confronting the health care systems. In diabetes mellitus (DM), combined use of oral hypoglycemic medications has been shown to be more effective than metformin (Met) alone in glycemic control. This study determined the effects of Ginkgo biloba (GKB) extract as an adjuvant to Met in patients with uncontrolled T2DM.Subjects and methods: Sixty T2DM patients were recruited in a randomized, placebo-controlled, double-blinded, and multicenter trial. The patients, currently using Met, were randomly grouped into those treated with either GKB extract (120 mg/day) or placebo (starch, 120 mg/day) for 90 days. Blood glycated hemoglobin (HbA1c), fasting serum glucose, serum insulin, body mass index (BMI), waist circumference (WC), insulin resistance, and visceral adiposity index (VAI) were determined before (baseline) and after 90 days of GKB extract treatment.Results: GKB extract significantly decreased blood HbA1c (7.7%±1.2% vs baseline 8.6%±1.6%, P<0.001), fasting serum glucose (154.7±36.1 mg/dL vs baseline 194.4±66.1 mg/dL, P<0.001) and insulin (13.4±7.8 µU/mL vs baseline 18.5±8.9 µU/mL, P=0.006) levels, BMI (31.6±5.1 kg/m2 vs baseline 34.0±6.0 kg/m2, P<0.001), waist WC (102.6±10.5 cm vs baseline 106.0±10.9 cm, P<0.001), and VAI (158.9±67.2 vs baseline 192.0±86.2, P=0.007). GKB extract did not negatively impact the liver, kidney, or hematopoietic functions.Conclusion: GKB extract as an adjuvant was effective in improving Met treatment outcomes in T2DM patients. Thus, it is suggested that GKB extract is an effective dietary supplement for the control of DM in humans. Keywords: T2DM, Ginkgo biloba extract, metformin, BMI, glycemic control, insulin resistance